Prediction of patellofemoral joint kinematics and contact through co-simulation of rigid body dynamics and nonlinear finite element analysis. Issue 11 (17th August 2020) - Müller, Jacobus H.; Razu, Swithin; Erdemir, Ahmet; Guess, Trent M.
Abstract: Joint-level rigid body dynamics simulations, when coupled with tissue-level finite element analyses, can simultaneously provide movement and tissue deformation metrics to understand mechanical interactions within the joint on a multi-scale level. In this study, a co-simulation workflow of a joint-level rigid body model that predicts the relative motion as a function of the non-linear cartilage response predicted by a non-linear implicit finite element solver is presented. Predictions are compared to in-vitro measurements (The Open Knee(s) project) in terms of the mean error and level-of-agreement: pressureerror = 0.46 MPa (level-of-agreement, −0.23 – 1.1 MPa); areaerror = −89 mm 2 (level-of-agreement, −280 – 98 mm 2 ) and contact forceerror = 93 N (level-of-agreement, 7.8 – 180 N). The automated co-simulation control algorithm enables multiscale coupling between joint and tissue-level models with real-time two-way communication as opposed to the traditional feed-forward approach of multi-scale models.